Combined Tide and Storm Influence on Facies Sedimentation of Miocene Miri Formation, Sarawak - Yuniarti Ulfa; Nasiman Sapari; Zuhar Zahir Tuan Harith (Pusat Teknologi Bahan Galian Nuklir - BATAN, 2011)
This study was conducted on the sedimentary rocks belonging to the Miri Formation (Middle – Late Miocene). The primary objective of the present study is to provide additional interpretation on the stratigraphy of the Miri Formation in the Miri Field based on the new information gathered from new outcrops in the area. Five outcrops were examined in detail on sedimentology and stratigraphy. Based on lithology, sedimentary structures, bedding geometry and traces fossil, the sediments of the Miri Formation were grouped into fourteen lithofacies. Influence of tide and storm during the depositional processes of the formation were indicated by the group of two main facies associations which are: (i) tide-dominated estuary; and (ii) wave-and-storm dominated facies associations. The tide-dominated estuary system of the Miri Formation are includes variety of sub environments: estuary mouth or tidal channel and sand bars (characterized by trough cross-stratified sandstone with mud drapes facies), estuary channel or upper flow regime of sand flat (characterized by parallel stratified sandstone with mud-laminas facies), mixed-tidal flat (characterized by wavy and flaser bedded sandstone facies), and mud-tidal flat (characterized by rhythmic stratified sandstone-mudstone and lenticular bedding facies). The wave-and-storm dominated varied from lower to middle shoreface (characterized by hummocky cross-stratified sandstone and rhythmic parallel stratified sandstone and laminated siltstone facies), upper shoreface (characterized by swaley cross-stratified sandstone), lower shoreface (interbedded to bioturbated sandstone and siltstone facies), and offshore transitional (characterized by bioturbated sandstone and mudstone interbedding with parallel to hummocky cross-stratified sandstone facies). Penelitian ini dilakukan pada batuan sedimen penyusun Formasi Miri (Miosen Tengah - Akhir). Tujuan penelitian ini adalah untuk mendapatkan interpretasi tambahan pada stratigrafi Formasi Miri di Lapangan Miri berdasarkan informasi baru yang dikumpulkan dari singkapan batuan baru di daerah tersebut. Lima singkapan tersebut diteliti secara rinci berdasarkan aspek sedimentologi dan stratigrafi. Berdasarkan litologi, struktur sedimen, geometri perlapisan dan fosil jejak, sedimen penyusun Formasi Miri dikelompokkan ke dalam empat belas litofasies. Pengaruh pasang surut dan badai selama proses pengendapan formasi diindikasikan dari adanya dua kelompok gabungan fasies utama antara lain: (i) didominasi oleh pasang-surut muara, dan (ii) didominasi oleh gabungan fasies gelombang dan badai. Sistem yang didominasi pasang surut muara pada Formasi Miri meliputi variasi sub-lingkungan: mulut muara atau alur pasang surut, dan gosong sungai (dicirikan oleh fasies batupasir dengan perlapisan saling silang dengan lempung yang mengapung), alur muara atau rezim aliran bagian atas dari dataran pasir (dicirikan oleh fasies batupasir berlapis paralel dengan lumpur berlapis), campuran pasang surut normal (dicirikan oleh fasies batupasir berlapis), dan lumpur pasang surut normal (dicirikan oleh fasies batupasir berlapis ritmik-batulumpur dan perlapisan lenticular). Dominasi pengaruh gelombang dan badai bervariasi dari rendah ke menengah (dicirikan oleh fasies batupasir berlapis silang yang hummocky dan batupasir berlapis paralel berulang dan batulanau berlapis), muka pantai bagian atas (dicirikan oleh batupasir berlapis silang yang swaley), muka pantai bagian bawah (fasies batupasir dan batulanau yang bersisipan sampai bioturtbasi), dan transisi lepas pantai (dicirikan oleh fasies batupasir bioturbasi dan batulumpur yang bersisipan dengan batupasir berlapis paralel sampai berlapis silang yang hummocky).